A new Polia Ochsenheimer, 1816 species from China (Lepidoptera, Noctuidae, Hadenini) - Saldaitis, Aidas; Benedek, Balázs; Behounek, Gottfried (Zootaxa, 2016)
The genus Polia Ochsenheimer, 1816 includes 26 species in the Palaearctic region, with the familiar European species being properly classified (Hacker et al., 2002), while most species from the more diverse Himalayan-region still require a comprehensive revision. Most recently, a new Polia species from China was described by Saldaitis et al. (2013). The sino-tibetian species Polia costirufa (Draudt, 1950) is one of the most interesting members of the complex as it is separable from its relatives at least on the subgeneric level. Certain elements of its forewing pattern resemble those of the genus Heliophobus Boisduval, but P. costirufa is much larger with more elongate forewings. While the P. costirufa male genital capsule shows typical Polia conservative features, the broad, sack-like vesica and the huge terminal cornutus are unique in the male and the large, elliptical and strongly sclerotised appendix bursae are unique female characters. The collective of the mentioned external and genital characters are suggesting the justifiable separation of P. costirufa from any other relatives, certainly on subgeneric level, but this would be better to integrate into a study incorporate the complete overview of the Polia-complex in the Himalayan region. P. costirufa male and female genitalia are described here for the first time but further study integrating this species into a complete overview of the Polia complex in the Himalayan region is recommended